Unsteady mixed convection flow over a cylinder of elliptic cross section near forward and rear stagnation points - Jamaludin, Madina (2011)
In this thesis, the unsteady mixed convection flow over a cylinder of elliptic cross section when the major axis are horizontal (blunt orientation) and vertical (slender orientation) have been studied. The study focused on the solution near the forward and rear stagnation points subjected to constant temperature placed in an incompressible viscous fluid. The unsteadiness is due to an impulsive motion of the free stream. The governing boundary layer equations are first reduced into a nondimensional form, and then, transformed into a set of non similarity boundary layer equations, which are solved numerically using an efficient implicit finite-difference method known as Keller-box method. The numerical results are obtained for various values of the Prandtl numbers, Pr, the mixed convection parameter, ? and parameter for blunt and slender orientation, ? . The effects of these parameter on velocity profiles, temperature profiles as well as Nusselt number are presented through graphs and tables. It is found that the increasing value of ? leads to a decreases in the velocity profiles for both cases, blunt and slender orientation near the forward and rear stagnation point, respectively. An increased value of temperature profiles is found near the forward stagnation point while the value is decreased near the rear stagnation point for the case of slender orientation. The temperature profiles are fixed for the case of blunt orientation. Further, near both the forward and rear stagnation points, it is also found that the Nusselt number is fixed with increasing ? for the case of blunt orientation. However, for the case of slender orientation, the Nusselt number near the forward stagnation point is decreased whereas near the rear stagnation point it is increased.